Cognitive decline according to amyloid uptake in patients with poststroke cognitive impairment. Issue 38 (24th September 2021) - Yoon, Bora; Yang, Dong Won; Hong, Yun-Jeong; Kim, Taewon; Na, Seunghee; Noh, Sang-Mi; Park, Hye Lim; Ku, Bon D.; Yang, Young Soon; Choi, Hojin; Jang, Jae-Won; Kim, Seongheon; et al.
Abstract: Background and purpose: Poststroke cognitive impairment (PSCI) is common, but the impact of β-amyloid (Aβ) on PSCI is uncertain. The proposed study will investigate amyloid pathology in participants with PSCI and how differently their cognition progress according to the amyloid pathology. Methods: This multicenter study was designed to be prospective and observational based on a projected cohort size of 196 participants with either newly developed cognitive impairment, or rapidly aggravated CI, within 3 months after acute cerebral infarction. They will undergo 18 F-flutemetamol positron emission tomography at baseline and will be categorized as either amyloid-positive (A+) or amyloid-negative (A−) by visual rating. The primary outcome measures will be based on Korean Mini-Mental State Examination changes (baseline to 12 months) between the A+ and A− groups. The secondary outcome measures will be the dementia-conversion rate and changes in the Korean version of the Montreal Cognitive Assessment (baseline to 12 months) between the A+ and A− groups. Conclusions: This study will provide a broadened perspective on the impact of Aβ on the cause and outcomes of PSCI in clinical practice. Identifying amyloid pathology in patients with PSCI will help select patients who need more focused treatments such as acetylcholinesterase inhibitors Trial registration: Clinical Research Information Service identifier: KCT0005086